Isolation and characterization marine bacteria capable of degrading lignin-derived compounds. - Peng Lu; Weinan Wang; Guangxi Zhang; Wen Li; Anjie Jiang; Mengjiao Cao; Xiaoyan Zhang; Ke Xing; Xue Peng; Bo Yuan; Zhaozhong Feng (PLoS ONE, 2020)
Lignin, a characteristic component of terrestrial plants. Rivers transport large amounts of vascular plant organic matter into the oceans where lignin can degrade over time; however, microorganisms involved in this degradation have not been identified. In this study, several bacterial strains were isolated from marine samples using the lignin-derived compound vanillic acid (4-hydroxy-3-methoxybenzoic acid) as the sole carbon and energy source. The optimum growth temperature for all isolates ranged from 30 to 35°C. All isolates grew well in a wide NaCl concentration range of 0 to over 50 g/L, with an optimum concentration of 22.8 g/L, which is the same as natural seawater. Phylogenetic analysis indicates that these strains are the members of Halomonas, Arthrobacter, Pseudoalteromonas, Marinomonas, and Thalassospira. These isolates are also able to use other lignin-derived compounds, such as 4-hydroxybenzoic acid, ferulic acid, syringic acid, and benzoic acid. Vanillic acid was detected in all culture media when isolates were grown on ferulic acid as the sole carbon source; however, no 4-hydroxy-3-methoxystyrene was detected, indicating that ferulic acid metabolism by these strains occurs via the elimination of two side chain carbons. Furthermore, the isolates exhibit 3,4-dioxygenase or 4,5-dioxygenase activity for protocatechuic acid ring-cleavage, which is consistent with the genetic sequences of related genera. This study was conducted to isolate and characterize marine bacteria of degrading lignin-derived compounds, thereby revealing the degradation of aromatic compounds in the marine environment and opening up new avenues for the development and utilization of marine biological resources.